A modular 3D printed microfluidic system: a potential solution for continuous cell harvesting in large-scale bioprocessing - Lin Ding; Sajad Razavi Bazaz; Mahsa Asadniaye Fardjahromi; Flyn McKinnirey; Brian Saputro; Balarka Banerjee; Graham Vesey; Majid Ebrahimi Warkiani (Bioresources and Bioprocessing, 2022)
Abstract Microfluidic devices have shown promising applications in the bioprocessing industry. However, the lack of modularity and high cost of testing and error limit their implementation in the industry. Advances in 3D printing technologies have facilitated the conversion of microfluidic devices from research output to applicable industrial systems. Here, for the first time, we presented a 3D printed modular microfluidic system consisting of two micromixers, one spiral microfluidic separator, and one microfluidic concentrator. We showed that this system can detach and separate mesenchymal stem cells (MSCs) from microcarriers (MCs) in a short time while maintaining the cell’s viability and functionality. The system can be multiplexed and scaled up to process large volumes of the industry. Importantly, this system is a closed system with no human intervention and is promising for current good manufacturing practices. Graphical Abstract